Risk Factors and Autoimmunity in Diet - A Narrative Review of Literature - Tenderenda, Maciej; Mularczyk, Zuzanna; Buczkowski, Bartosz; Nowakowski, Krzysztof; Śmigiel, Aleksandra; Broniak, Aleksandra (Quality in Sport, 2025)
Introduction The role of dietary factors in modulating immune function and influencing the risk and progression of autoimmune diseases has recently gained increasing attention. Western-style dietary factors, rich in processed foods, saturated fatty acids, and refined sugars, have been implicated in promoting systemic low-grade inflammation and contributing to gut dysbiosis, while anti-inflammatory diets may offer protective benefits. Better understanding of diet and its impact on the immune system may offer new therapeutic avenues to explore in the near future. Materials and Methods A literature review was performed using four major scientific databases: PubMed, Elsevier, Web of Science, and Scopus. A total of 72 research and review articles relevant to the topic were selected based on predefined inclusion criteria. The selection criteria were based upon key words: autoimmune diseases, diet, inflammation, gut microbiota, micronutrients, Western diet, Mediterranean diet, omega-3 fatty acids. Basic Results Diets high in processed foods, saturated fatty acids, and high-glycemic index foods contribute to the development and maintenance of chronic inflammation, oxidative stress, and gut microbiota dysbiosis. Conversely, diets rich in polyphenols, flavonoids, fibers, and omega-3 fatty acids, promote immune tolerance and maintain the balance between anty- and proinflammatory factors. Conclusions Nutritional interventions may serve as supportive strategies for prevention and management of autoimmune diseases. Understanding dietary risk factors and implementing targeted nutritional modifications in the future could improve patients’ outcomes.